On the Existence of Positive Solutions for a Fourth-Order Boundary Value Problem. (14th August 2017) - Zou, Yumei
Abstract : By using the method of order reduction and the fixed point index, the existence of positive solutions for a fourth-order boundary value problem is studied. We provide conditions under which the existence results hold. Such conditions are related to the first eigenvalue corresponding to the relevant linear differential equation with dependence on the derivatives of unknown function.